Prescribing Trends Of Antidiabetics In Diabetic Patients And Hypertensive Diabetic Patients In An Urban Secondary Care Hospital - Sachdeva, Punam (International Journal of Pharmaceutical & Biological Archive, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Background: Diabetes is a chronic illness associated with significant morbidity and mortality. Diabetics are at a higher risk of polypharmacy and more vulnerable to irrational prescribing especially diabetics suffering from concurrent illnesses like hypertension. Objectives: The present study was conducted with the objectives of providing an insight into the current use of antidiabetic medications to diabetics and hypertensive diabetics in urban areas and determining how the patient factors influence the prescribing of antidiabetic medications. Methods: A retrospective epidemiological study was arried out at Out-Patient Department (OPD) at Shri Vraj Hospital, Baroda, Gujarat, India, from January 2008 to March 2008. Data of patients of past two years were collected. The details were entered in the structured patient profile form. Data were statistically analyzed using the SPSS software. Results: Data of 492 patients were collected and analyzed of which 334 (67.88 %) were males and 158 (32.11 %) were females. These patients were further categorized based on their age. 126 patients (25.6 %) belonged to the age group 20 - 44 years, 294 (59.75 %) to the age group 45 - 65 years and 72 (14.6 %) to the age group 65 – 80 years. 246 (50%) patients out of the 492 patients studied were suffering from coexisting hypertension. Co-existing hypertension was found to be more prevalent in the age group 45 - 65 years (59.75%) and its incidence was found to be more in females (56.32%). Metformin was the oral hypoglycemic which was the highest prescribed. Metformin and Acarbose were prescribed to obese patient. Sulphonylureas and thiazolidnediones were prescribed less in obese patient. In elderly patients sulphonylureas were prescribed less. In hypertensive diabetics Metformin and Pioglitazone were most frequently prescribed drugs. Monotherapy was prescribed for 11.3% patients and remaining patients were prescribed combination therapy. Conclusion: Biguanides and Insulin were the most commonly prescribed antidiabetics. A combination of two or more drugs of different classes was prescribed to hypertensive diabetics. Since the scope of the present study is limited as the number of patients studied is less, extensive studies are required to confirm our findings.